Incidencia de los embarazos prematuros en el nivel de rendimiento de las estudiantes de los Colegios del cantón Pasaje, caso. Instituto Superior Tecnológico Dr. José Ochoa León Colegio Técnico Nacional Carmen Mora de Encalada, periodo lectivo 2009-2010. - Alvarado Espinosa, Eufemia Judith (2010)
The research was oriented, depending on the incidence of premature pregnancies in the performance level of students of the Institute Dr. José Ochoa Leon and Carmen Mora whitewashed College, Canton Pasaje, assuming that as to be reduced the premature pregnancies the level of academic performance of students improved teaching and learning process.